Open Innovation in Health Service Value Networks: a Methodology for the Innovation of Ambient Assisted Living Platforms and Services - Meersman, Davor; De Leenheer, P (Springer, 2012)
In this paper we introduce a methodology for collaborative innovation in the ambient assisted living domain using service value networks. We look to solve problems associated with heterogeneity, domain knowledge formalisation, low acceptance, integration and immaturity in the ambient assisted living domain. Our methodology consists of domain elicitation and modelling, needs elicitation and laddering, atomisation, recombination, and deployment and monitoring.